HUBUNGAN CITRA TUBUH DENGAN PENYESUAIAN DIRI PADA REMAJA DI INDONESIA - Oky Istiowati; Eppy Setiyowati; Lucky Ramadhani; Yuliawati, Yuliawati; Sal Sabilla Heni Nurdia; Firda Datil Amalia; Dessy Eka Safitri (Jurnal Ilmu Kesehatan dan Gizi, 2023)
Body image is a view of the individual's psychology of the physical the individual perceives and gives an assessment of things that have been observed by a person, from perceptions and judgments of other individuals. The purpose of this research is to determine the relationship between body image and adolescent self-adjustment in Indonesia. Quantitative method with Croos Sectional research using purposive sampling technique. The research population is teenagers, totaling 38 teenagers. The inclusion criteria were healthy youth, able to read and write, literate and aged between 10-24 years. The instrument uses a questionnaire, the results of the respondents' answers are processed using SPSS Ver. 27. The results of the study conclude Appearance Evaluation, Strongly disagree (5.3%), Disagree (13.2%), Neutral (28.9%), Agree (36.8%), Strongly agree (15.8%) ), Control over excessive emotions with the number of respondents who answered as much as (44.7%), Realistic and objective attitudes of the number of respondents (52.6%). The conclusion is that body image problems with obesity in Indonesia are still relatively high, 31.6% are obese, while 57.9% are not obese. Which has an impact on a teenager's self-adjustment, which aims to determine the relationship between body image and adolescent self-adjustment.